2021
DOI: 10.1111/cdoe.12674
|View full text |Cite
|
Sign up to set email alerts
|

Determining the factors associated with oral health‐related quality of life in Chinese elders: Findings from the fourth national survey

Abstract: Objective:The purpose of this study was to assess the associations between the selfreported oral health-related quality of life (OHRQoL) of older Chinese people and their socio-economic status and oral health using data collected in the 4th National Oral Health Survey.Methods: After multistage stratified cluster sampling, 4332 adults aged 65-74 years participated in the study. After a clinical examination, the participants completed a structured questionnaire. A Mandarin version of the General Oral Health Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…For example, findings from a cross-sectional study in Hong Kong demonstrated lower household income, divided into income groups, was significantly associated with higher score in the OHIP-14, therefore representing worse OHRQoL [ 17 ]. Similarly, results from the 4th National Oral Health Survey among over 4000 Chinese adults showed that participants with higher household income per capita had better OHRQoL [ 18 ]. The negative impact of low household income on a person’s OHRQoL has also been reported among adolescents [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, findings from a cross-sectional study in Hong Kong demonstrated lower household income, divided into income groups, was significantly associated with higher score in the OHIP-14, therefore representing worse OHRQoL [ 17 ]. Similarly, results from the 4th National Oral Health Survey among over 4000 Chinese adults showed that participants with higher household income per capita had better OHRQoL [ 18 ]. The negative impact of low household income on a person’s OHRQoL has also been reported among adolescents [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,26 Caries risk assessment is a fundamental measure in the screening of people with a high risk of caries to facilitate prevention. 27 There are two main types of CRA, namely, reasoning-based programs (CAT and CAMBRA) and algorithm-driven programs Dental caries is a multifactorial disease and CRA tools usually include multiple risk factors and protective factors in a prediction system. In the current study, children's dietary habits (e.g., consumption of cookies and cakes) and oral hygiene (e.g., frequency of tooth brushing) were validated as significant predictive factors, which was consistent with many previous investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Caries risk assessment is a fundamental measure in the screening of people with a high risk of caries to facilitate prevention. 27 There are two main types of CRA, namely, reasoning-based programs (CAT and CAMBRA) and algorithm-driven programs (Cariogram and NUS-CRA). 16 However, no CRA model can accurately predict whether an individual will develop caries at a certain time.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that lower OHRQoL in older adults is associated with increased age, sex, socioeconomic disadvantage, anxiety or depression, negative self-rated general health, poor oral health, lack of dentures, dry mouth, poor chewing and swallowing function, and irregular dental visits [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Poor nutritional status has also a deleterious effect on OHRQoL [ 5 ].…”
Section: Introductionmentioning
confidence: 99%